The Autonomous Vehicle CELiNA as Educational Platform on Final Works in Computer Science - Andrade, Alexsandra; Trindade, Roque; Silva, Alzira; Gonçalves, Luiz (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
This work introduces the design and construction of the autonomous vehicle CELiNA (Free Electric Car with Autonomous Navigation) qualitatively analyzing its use on educational experiences that have been carried out with Computer Science course students of the University of the Southwest of Bahia (UESB). As a result of its use, several works have been carried out in the course conclusion activity, which include the construction of the CELiNA prototype and other studies regarding robotic vision system and the control of CELiNA, itself. We discuss the educational gains that these UESB students have had at the end of the course, by way of using CELiNA in their completion work.